2019
DOI: 10.1111/1462-2920.14586
|View full text |Cite
|
Sign up to set email alerts
|

A new chromosomal rearrangement improves the adaptation of wine yeasts to sulfite

Abstract: Summary Sulfite‐generating compounds are widely used during winemaking as preservatives because of its antimicrobial and antioxidant properties. Thus, wine yeast strains have developed different genetic strategies to increase its sulfite resistance. The most efficient sulfite detoxification mechanism in Saccharomyces cerevisiae uses a plasma membrane protein called Ssu1 to efflux sulfite. In wine yeast strains, two chromosomal translocations (VIIItXVI and XVtXVI) involving the SSU1 promoter region have been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 53 publications
2
50
2
Order By: Relevance
“…Among them are sulfite reduction, sulfite oxidation, acetaldehyde production, sulfite efflux, and behaving as viable but not culturable cells [20]. In addition, SO 2 tolerance has been connected to a molecular mechanism which involves a higher transcription level of the SSU1 gene [21][22][23]. The molecular mechanisms involved in CO 2 pressure tolerance have only very recently been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Among them are sulfite reduction, sulfite oxidation, acetaldehyde production, sulfite efflux, and behaving as viable but not culturable cells [20]. In addition, SO 2 tolerance has been connected to a molecular mechanism which involves a higher transcription level of the SSU1 gene [21][22][23]. The molecular mechanisms involved in CO 2 pressure tolerance have only very recently been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, translocation events (i.e., XV-t-XVI and VIII-t-XVI) have been detected by classical PCR experiments narrowing the chromosomal break points identified by two original works (Pérez-Ortín et al, 2002; Zimmer et al, 2014). Recently, an additional chromosomal rearrangement involving the gene SSU1 (inv-XVI) was also described (García-Ríos et al, 2019). Since these classical PCR amplifications are scarcely adapted to screen multiple genotypes in large populations, a multiplexed method ( SSU1 checkup ) was set up aiming to identify, in a single PCR reaction, these three types of chromosomal rearrangements (VIII-t-XVI, XV-t-XVI and inv-XVI) as well as the wild type alleles of the corresponding chromosomes (VIII-wt, XV-wt and XVI-wt).…”
Section: Resultsmentioning
confidence: 99%
“…These experiments discarded the hypothesis of a partial annealing of primers. The recent report of a new chromosomal rearrangement (inv-XVI) involving the gene SSU1 (García-Ríos et al, 2019), prompted us to include this new allelic form of the gene SSU1 to our screening (see Figure 1). Of the 39 strains concerned, this chromosomal inversion was detected in 19 natural isolates and showed a single allele of 781 bp (inv-XVI 781 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies about the mechanism of sulfite resistance, identified a chromosomal translocation ( Figure 1B ) and non-homologous recombination of the SSU1 gene promoter ( Pérez-Ortín et al, 2002 ). Moreover, a chromosomal inversion between XVI and VIII connected with the SSU1 regulatory region also result in overexpression of SSU1 and thus in sulfite resistance to commercial wine strains ( García-Ríos et al, 2019b ).…”
Section: Copy Number Variations and Re-arrangementsmentioning
confidence: 99%